Beethoven's 32 piano sonatas a handbook for performers - Gordon, Stewart 1930- (New York Oxford University Press, 2017)
"The thirty-two piano sonatas of Ludwig van Beethoven comprise one of the most important parts of the piano literature, yet true mastery of these works can be elusive to even the most seasoned performer. With years of experience performing and teaching the literature and intimate knowledge of the works, their history and context, renowned pianist and pedagogue Stewart Gordon guides today's pianist performer through each of the thirty-two sonatas in stunning detail."--Page 4 of cover.
Part I : Considerations. Sources -- Beethoven and the piano -- Performance practices -- Beethoven's expressive legacy -- The windmills of Beethoven's mind -- Part II : The sonatas. The Opus 2 set -- Opus 7 -- The Opus 10 set -- Opus 13 ("Pathâetique") -- The Opus 14 set -- Opus 22 -- Opus 26 -- The Opus 27 set : sonatas like a fantasy; no.2 ("Moonlight") -- Opus 28 ("Pastoral") -- The Opus 31 set no.2 ("Tempest"); no.3 ("Hunt") -- The Opus 49 set : two "easy" sonatas -- Opus 53 ("Waldstein") -- Opus 54 -- Opus 57 ("Appassionata") -- Opus 78 -- Opus 79 ("alla tedesca") -- Opus 81a ("Lebewohl") -- Opus 90 -- Opus 101 -- Opus 106 ("Hammerklavier") -- Opus 109 -- Opus 110 -- Opus 111.
Includes bibliographical references (pages 267-268) and index.
Keywords: Piano music -- Interpretation (Phrasing, dynamics, etc.); Performance practice(Music); Sonatas (Piano) -- Analysis, appreciation